A rapid and automated relocation method of an AFM probe for high-resolution imaging. (25th August 2016) - Zhou, Peilin; Yu, Haibo; Shi, Jialin; Jiao, Niandong; Wang, Zhidong; Wang, Yuechao; Liu, Lianqing
Abstract: The atomic force microscope (AFM) is one of the most powerful tools for high-resolution imaging and high-precision positioning for nanomanipulation. The selection of the scanning area of the AFM depends on the use of the optical microscope. However, the resolution of an optical microscope is generally no larger than 200 nm owing to wavelength limitations of visible light. Taking into consideration the two determinants of relocation—relative angular rotation and positional offset between the AFM probe and nano target—it is therefore extremely challenging to precisely relocate the AFM probe to the initial scan/manipulation area for the same nano target after the AFM probe has been replaced, or after the sample has been moved. In this paper, we investigate a rapid automated relocation method for the nano target of an AFM using a coordinate transformation. The relocation process is both simple and rapid; moreover, multiple nano targets can be relocated by only identifying a pair of reference points. It possesses a centimeter-scale location range and nano-scale precision. The main advantages of this method are that it overcomes the limitations associated with the resolution of optical microscopes, and that it is label-free on the target areas, which means that it does not require the use of special artificial markers on the target sample areas. Relocation experiments using nanospheres, DNA, SWCNTs, and nano patterns amply demonstrate the practicality and efficiency of the proposed method, which provides technical support for mass nanomanipulation and detection based on AFM for multiple nano targets that are widely distributed in a large area.